1989
DOI: 10.1007/bf00393857
|View full text |Cite
|
Sign up to set email alerts
|

Rhodospirillum centenum, sp. nov., a thermotolerant cyst-forming anoxygenic photosynthetic bacterium

Abstract: A novel non-sulfur purple photosynthetic bacterium, designated Rhodospirillum centenum, was isolated from an enrichment culture designed to favor growth of anoxygenic photosynthetic N2-fixing bacteria. R. centenum grows optimally at 40-42 degrees C and has the capacity to produce cytoplasmic 'R bodies', refractile structures not observed hitherto in photosynthetic prokaryotes. The bacterium is also unusual among photosynthetic bacteria in that it forms desiccation-resistant cysts when grown aerobically in dark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
89
0

Year Published

1991
1991
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 126 publications
(90 citation statements)
references
References 8 publications
1
89
0
Order By: Relevance
“…The wild-type strain of R. centenum used in this study (ATCC 43720) is a thermotolerant nonsulfur purple bacterium isolated from Thermopolis Hot Springs, Wyo. (6). R. centenum FY040, that fails to synthesize a reaction center complex, and FY013, which exhibits oxygen repression of pigment biosynthesis, have been described previously (18).…”
Section: Methodsmentioning
confidence: 94%
See 2 more Smart Citations
“…The wild-type strain of R. centenum used in this study (ATCC 43720) is a thermotolerant nonsulfur purple bacterium isolated from Thermopolis Hot Springs, Wyo. (6). R. centenum FY040, that fails to synthesize a reaction center complex, and FY013, which exhibits oxygen repression of pigment biosynthesis, have been described previously (18).…”
Section: Methodsmentioning
confidence: 94%
“…R. centenum FY040, that fails to synthesize a reaction center complex, and FY013, which exhibits oxygen repression of pigment biosynthesis, have been described previously (18). R. centenum strains were routinely grown at 42°C in CENMED, a synthetic minimal medium containing pyruvate as the carbon source (6), or in CENS medium, which consists of CENMED supplemented with 0.4% Difco Soytone (13 Extraction of pigments. The total bacteriochlorophyll (Bchl) a content of cells was measured by extracting pigments from cell pellets with cold acetone-methanol (7:2) as described previously (3).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…55°C) of the source pool at Thermopolis Hot Springs, Wyoming, U.S.A. (4). The bacterium is unusual among anoxygenic phototrophic bacteria in possessing cytoplasmic `R-body' and forming desiccation-and heat-resistant cysts when grown under aerobic conditions in the dark (4).…”
Section: Spirillummentioning
confidence: 99%
“…The bacterium is unusual among anoxygenic phototrophic bacteria in possessing cytoplasmic `R-body' and forming desiccation-and heat-resistant cysts when grown under aerobic conditions in the dark (4). Favinger et al (4) reported the bacterium to be a member of the genus Rhodospirillum on the bases of vegetative cell morphology and biochemical properties. However, the cyst-formation is a unique character and implies the possibility that the bacterium is not a member of the genus Rhodospirillum.…”
Section: Spirillummentioning
confidence: 99%